The Opportunities of Working in a Challenging Environment. Issue 1 (23rd August 2021) - Muluneh, Ameha Atnafu
Abstract: A few days after the American Geophysical Union announced that I am the recipient of the 2020 Africa Award for research excellence in Earth or Ocean Sciences, I received an email from Michael Wysession, editor‐in‐chief of Perspectives of Earth and Space Scientists, to write a story about my scientific experiences. I was filled with emotions. I never thought of sharing my experience with other people (except to my wife and children and close friends). I hope my story will inspire mainly marginal students, who may think that society will exclude them owing to western credentials, and believe that they cannot achieve a spot in science because of their grades. I strongly believe that scientific excellence is achieved by hard work (mostly in a subject area that you like), and a little bit of good luck. Plain Language Summary: Hard work and a little bit of luck are important to secure a spot in academia. Most of the decisions in my professional life have been made by circumstances but I tried to make the best out of them. Key Points: Hard work and a little bit of luck are important to pursue a career in science Most decisions in professional life might be made by circumstances, but try to make the best out of them